Values, early childhood education and moral development: teachers’ conceptions - Lima, Juliana dos Santos (2018)
In the current Brazilian society, morality is emerging as one of the most important issues challenging educational practices. The goal of the study is to understand how preschool teachers conceive of the values relative to their pedagogical practices and the moral development of children. It is a qualitative research, which uses the semi-structured interview for the production of information. The participants are eight educators of early childhood education in a public school located in Jaguarari, a small city in Bahia. The results show that the values appear in the speeches and actions of teachers, as well as in the activities they propose to students, although they try to wriggle out of responsibility. The professors are careful in relationship with the students, but this relationship is asymmetrical and prioritizes the duty, the unilateral respect and obedience. This means that teachers take an adult-centered position in their practices.